2015
DOI: 10.1016/j.adolescence.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations between loneliness and emotional intelligence

Abstract: Loneliness has been linked cross-sectionally to emotional skill deficits (e.g., Zysberg, 2012), but missing from the literature is a longitudinal examination of these relationships. The present study fills that gap by examining the prospective relationships between loneliness and emotional functioning in young adolescents in England. One hundred and ninety-six adolescents aged 11-13 years (90 females) took part in the study and completed the youth version of the Mayer-Salovey-Caruso Emotional Intelligence Test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 56 publications
4
35
1
2
Order By: Relevance
“…EA was also significantly and positively related to loneliness. These results supported our hypotheses and were consistent with previous findings related to emotion regulation and loneliness [15, 16, 49, 68]. Particularly, the current study suggested that, within Chinese culture, individuals with low levels of ERA were more likely to have a greater tendency to engage in EA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…EA was also significantly and positively related to loneliness. These results supported our hypotheses and were consistent with previous findings related to emotion regulation and loneliness [15, 16, 49, 68]. Particularly, the current study suggested that, within Chinese culture, individuals with low levels of ERA were more likely to have a greater tendency to engage in EA.…”
Section: Discussionsupporting
confidence: 93%
“…Recent empirical studies have uncovered a close relationship between emotional skills, such as emotional intelligence, and loneliness [1517]. The findings showed that poor emotional skills increase loneliness over time [15, 16, 18]. Similarly, if people could effectively perceive and manage negative feelings associated with loneliness, they could successfully overcome loneliness [19].…”
Section: Introductionmentioning
confidence: 99%
“…And second, levels of repair at the end of the course will decrease loneliness in the next course. Previous research on emotional intelligence found support for the model proposed by Cacioppo and Hawkley (), which states that poor emotional skills increase loneliness over time (Wols, Scholte, & Qualter, ; Zysberg, ), denoting a negative relation between repair and loneliness, as we had hypothesized (Hypothesis d). Nevertheless, it is noteworthy that, beyond the small size of the results, initial levels of repair at the beginning of the course will increase loneliness.…”
Section: Discussionsupporting
confidence: 77%
“…Our finding that ESE predicted school belongingness and peer loneliness supports evidence from previous studies showing that the ability to manage emotions is important for adjustment to secondary school (Adeyemo, ; Qualter et al ., ) and feelings of belonging (Wols, Scholte, & Qualter, ). Thus, building emotional skills and increasing children's confidence in using those skills is important for ensuring children's adjustment during school transition.…”
Section: Discussionmentioning
confidence: 99%